2019
DOI: 10.1002/jia2.25260
|View full text |Cite
|
Sign up to set email alerts
|

Going off antiretroviral treatment in a closely monitored HIV “cure” trial: longitudinal assessments of acutely diagnosed trial participants and decliners

Abstract: Introduction The South East Asia Research Collaboration in HIV (SEARCH) RV411 clinical trial in Thailand was a systematic investigation of analytic treatment interruption (ATI) in individuals diagnosed and treated since Fiebig stage I acute HIV infection. Here, we explore decision‐making processes and perceptions of trial participation in a phase I trial that raised important ethical considerations, to identify potential areas of improvement in this relatively new field of HIV research. Similar considerations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(51 citation statements)
references
References 21 publications
1
50
0
Order By: Relevance
“…The ongoing RV254/SEARCH010 cohort in Bangkok has proven to be fertile ground for the development and implementation of HIV remission trials, leveraging evidence that the lower reservoir size and preserved immune function of individuals who start ART during acute infection might facilitate viral control in the absence of ART. The study has shown that execution of observational and interventional research during the period surrounding acute HIV infection is safe, feasible, and acceptable to participant populations [55, 56]. This includes research that involves invasive procedures such as lumbar puncture and lymph node biopsy [57, 58].…”
Section: Introductionmentioning
confidence: 99%
“…The ongoing RV254/SEARCH010 cohort in Bangkok has proven to be fertile ground for the development and implementation of HIV remission trials, leveraging evidence that the lower reservoir size and preserved immune function of individuals who start ART during acute infection might facilitate viral control in the absence of ART. The study has shown that execution of observational and interventional research during the period surrounding acute HIV infection is safe, feasible, and acceptable to participant populations [55, 56]. This includes research that involves invasive procedures such as lumbar puncture and lymph node biopsy [57, 58].…”
Section: Introductionmentioning
confidence: 99%
“…Supportive BSSR also includes understanding how participants make decisions to participate in HIV cure research. With the support of biomedical HIV cure research teams, socio‐behavioural scientists are increasingly able to understand decision‐making processes of those who decide to participate (or not) in HIV cure research, rather than relying on hypothetical intentions and perceptions . Supportive BSSR may also include patient‐reported outcomes (PROs) and patient‐reported experience measures (PREMs) completed by participants to assess the effects of study participation on various critical domains, such as well‐being, symptoms, functioning, adverse events and experiences with interventions, studies and ATIs .…”
Section: Discussionmentioning
confidence: 99%
“…BSSR methods can help the field come to consensus around critical parameters and safeguards to maximize ATIs' utility while minimizing risks . Supportive BSSR can also help in understanding various aspects of informed consent related to HIV cure research, including how participants understand the risks and benefits of research . BSSR can provide strategies to measure adherence or non‐adherence to ART and ATIs .…”
Section: Discussionmentioning
confidence: 99%
“…Overall, she finds that both groups scored highly on a measure incorporating self-assessed informational clarity, support in decision-making and satisfaction with a choice. She also found that all eight of those who did participate in the research were initially motivated in part by the prospect of stopping ART, all eight reported elements of the treatment interruption as positive and all eight remained satisfied with their initial choice 9 13 …”
Section: Short Well-monitored Treatment Interruptionsmentioning
confidence: 97%